The truth about talent : a guide to building a dynamic workforce, realizing potential and helping leaders succeed - Davies, Jacqueline, 1970- (Jossey-Bass, 2010)
"Understanding the truth about talent in all forms is a vital step in developing a long-term, sustainable, successful organization. The Truth about Talent explores the different ways for organizations to recognize talent from people at different stages of their career, as well as from people with different experiences and aspirations. With a forward-thinking approach, this resource provides qualitative and quantitative international research on talent management and employee engagement, as well as an original survey of executives. This book shows the fundamental changes in line to enhance employees and the economy"--